Горе от ума - Грибоедов Александр Сергеевич (КиС (Классическая и Современная литература), 2023)
Экземпляры: (20231003) / Инвентарный номер: 42645 / Цена: 520.00 / Сис.шифр: 84(2=411.2)1 / Авт.знак: Г 82 / ГРНТИ: 17.82.20 / ББК: 84(2=411.2)1